Photothermal Performance of 2D Material-Based Nanoparticles for Biomedical Applications - Amir Eghbali; Nikolay V. Pak; Aleksey V. Arsenin; Valentyn Volkov; Andrey A. Vyshnevyy (Nanomaterials)
Photothermal therapy (PTT) is one of the rapidly developing methods for cancer treatment based on the strong light-to-heat conversion by nanoparticles. Over the past decade, the palette of photonic materials has expanded drastically, and nanoparticle fabrication techniques can now preserve the optical response of a bulk material in produced nanoparticles. This progress potentially holds opportunities for the efficiency enhancement of PTT, which have not fully explored yet. Here we study the photothermal performance of spherical nanoparticles (SNs) composed of novel two-dimensional (2D) and conventional materials with existing or potential applications in photothermal therapy such as MoS2, PdSe2, Ti3C2, TaS2, and TiN. Using the Mie theory, we theoretically analyze the optical response of SNs across various radii of 5–100 nm in the near-infrared (NIR) region with a particular focus on the therapeutic NIR-II range (1000–1700 nm) and radii below 50 nm. Our calculations reveal distinct photothermal behaviors: Large (radius > 50 nm) nanoparticles made of van der Waals semiconductors and PdSe2 perform exceptionally well in the NIR-I range (750–950 nm) due to excitonic optical responses, while Ti3C2 nanoparticles achieve broad effectiveness across both NIR zones due to their dual dielectric/plasmonic properties. Small TiN SNs excel in the NIR-I zone due to the plasmonic response of TiN at shorter wavelengths. Notably, the van der Waals metal TaS2 emerges as the most promising photothermal transduction agent in the NIR-II region, particularly for smaller nanoparticles, due to its plasmonic resonance. Our insights lay a foundation for designing efficient photothermal transduction agents, with significant implications for cancer therapy and other biomedical applications.